2010
DOI: 10.1152/ajpcell.00430.2009
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular osmolarity modulates G protein-coupled receptor-dependent ATP release from 1321N1 astrocytoma cells

Abstract: We previously reported that ATP release from 1321N1 human astrocytoma cells could be stimulated either by activation of G protein-coupled receptors (GPCR) or by hypotonic stress. Cheema et al. (Cheema TA, Ward CE, Fisher SK. J Pharmacol Exp Ther 315: 755-763, 2005) have demonstrated that thrombin activation of protease-activated receptor 1 (PAR1) in 1321N1 cells and primary astrocytes acts synergistically with hypotonic stress to gate the opening of volume-sensitive organic osmolyte and anion channels (VSOAC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 77 publications
1
26
0
Order By: Relevance
“…VRAC Cl − channel activity is activated in response to osmotic cell swelling and inhibited by a broad spectrum of reagents, including glibenclamide, verapamil, tamoxifen, fluoxetine, nordihydroguaiaretic acid, dideoxyforskolin, niflumic acid, quinine, NPPB, DIDS, and SITS [101,105]. VRAC inhibitors suppressed ATP release in aortic endothelial cells [102] and 1321N1 astrocytoma cells [105], but not in Intestine 407 cells [106] or alveolar or airway epithelial cells [73]. Recently, bradykinin-stimulated astrocytes exhibited VRAC-like activity that was associated with the release of glutamate but not ATP [107].…”
Section: Atp Conducting CLmentioning
confidence: 99%
“…VRAC Cl − channel activity is activated in response to osmotic cell swelling and inhibited by a broad spectrum of reagents, including glibenclamide, verapamil, tamoxifen, fluoxetine, nordihydroguaiaretic acid, dideoxyforskolin, niflumic acid, quinine, NPPB, DIDS, and SITS [101,105]. VRAC inhibitors suppressed ATP release in aortic endothelial cells [102] and 1321N1 astrocytoma cells [105], but not in Intestine 407 cells [106] or alveolar or airway epithelial cells [73]. Recently, bradykinin-stimulated astrocytes exhibited VRAC-like activity that was associated with the release of glutamate but not ATP [107].…”
Section: Atp Conducting CLmentioning
confidence: 99%
“…Similarly, changes in the extracellular osmolarity induced by hypotonic solution may also stimulate interaction of pannexin1 hemichannels with other membrane proteins in liver cells, and this may result in the decreased sensitivity to CBX and probenecid. A recent study in 1321 N1 astrocytes provides evidence for this explanation [38]. The authors found that extracellular osmolarity modulates the sensitivity of thrombin-dependent ATP release to probenecid.…”
Section: Discussionmentioning
confidence: 95%
“…Regulated ATP release occurs in most mammalian cells under stressed or stimulated conditions such as mechanical stress (8,9), hypoxia (10,11), lysophospholipids (12), and agonist stimulation (9). Static unstimulated cells also release ATP (13), and it was shown that the extracellular ATP concentration ([ATP] o ) was three times higher in thyroid cancer cell lines than in normal thyroid cells (14).…”
Section: Introductionmentioning
confidence: 99%